Prevalence of COVID-19 fear and its association with quality of life among fire service recruits after ceasing the dynamic zero-COVID policy in China - Liu, Jian; Si, Tong Leong; Chen, Pan; Wang, Yue-Ying; Su, Zhaohui; Cheung, Teris; Jackson, Todd; Xiang, Yu-Tao; Feng, Yuan (Frontiers in Public Health, 2023)
Background In December 2022, China terminated its dynamic zero-COVID policy. To date, however, no research has been conducted upon mental health issues and their relationship with quality of life (hereafter QoL) among fire service recruits since the dynamic zero-COVID policy ended. This study explored fear of COVID-19 (FOC) prevalence and correlates as well as its network structure and interconnections with QoL among fire service recruits. Methods A cross-sectional survey design was used to assess fire service recruits in Beijing and Sichuan, Guangxi and Guizhou provinces of China between February 13 and 16, 2023. Fear of COVID-19 was measured using the Fear of COVID-19 Scale, depression was assessed with the Patient Health Questionnaire, anxiety was examined using the Generalized Anxiety Disorder scale, and QOL was evaluated with the World Health Organization Quality of Life-brief version. Univariate and multivariate analyses were used to explore correlates of COVID-19 fear. Network analysis assessed the structure of fear of COVID-19 and its associations with QoL. Results A total of 1,560 participants were included in this study. The overall prevalence of fear of COVID-19 was 38.85% (n = 606; 95% CI = 36.42–41.32%). Being afraid of COVID-19 was significantly related to depression (OR = 1.084; p < O.OO1) and physical fatigue (OR = 1.063; p = 0.026). Fire service recruits with more fear of COVID-19 had lower QOL (F = 18.061 p < 0.001) than those with less fear of COVID-19 did. The most central symptoms included FOC6 (“Sleep difficulties caused by worry about COVID-19”), FOC7 (“Palpitations when thinking about COVID-19”) and FOC2 (“Uncomfortable to think about COVID-19”). The top three symptoms negatively associated with QoL were FOC4 (“Afraid of losing life because of COVID-19”), FOC6 (“Sleep difficulties caused by worry about COVID-19”) and FOC2 (“Uncomfortable to think about COVID-19”). Conclusion Over one-third of fire service recruits reported fear of COVID-19 after China’s dynamic zero-COVID policy had terminated. Poorer QoL was related to fear of COVID-19. Targeting core symptoms of the fear network structure could help improve the physical and mental health of fire service recruits during public health crises.